Pengaruh Consumer Knowledge, Brand Image, Religiusitas, dan Lokasi Terhadap Keputusan Menjadi Nasabah Pada Bank Syariah - Afrian Rachmawati; Gusti Oka Widana (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2019)
For the last decades, sharia banking in Indonesia has not reached a good position, in which, based on the last data, sharia banking’s market share is only 5.70%. This research focuses on distributing questionnaires in Banten Province as one of some provinces with its majority citizens are Muslims, namely at 94.62% from a total of 12,448,160 citizens. It is related to a high potential market for sharia banking to develop its business in the Banten Province area. Assets of the sharia banking in Banten Province continuously increased in the last 4 (four) years from 2015 to 2018. The sharia banking’s assets grew 2.35%, namely the 7th position of 10 provinces with the highest asset values. For the last four years, from 2015 to 2018, sharia banking’s third-party funds of Banten Province continuously increased. Whereas, the NPF growth of Banten Province as per June 2018 was 2.03%, in which it was deficient compared to NPF of West Java, Special Region of Jakarta, and Central Java. This research is aimed at analyzing the influence of consumer knowledge, brand image, religiosity, and location to any decision to be sharia bank’s customer by using four hypotheses to be examined using the SEM method. The research sample includes 212 respondents. Results of SEM analysis meet the criteria of goodness of fit index with marginal. The results of this research show that consumer knowledge with product type, product use, and product benefit indicators do not significantly influence the decision to be sharia bank’s customer. Brand image with product attributes, consumer benefit, and brand personality indicators do not significantly influence the decision to be sharia bank’s customer. Religiosity with ritual, ideology, intellectual, experience, and consequence indicators do not significantly influence any decision to be sharia bank’s customer. Location with location accessibility, location smoothness, and location proximity indicators significantly influence any decision to be sharia bank’s customer.